Policy and Investment Priorities to Reduce Environmental Degradation of the Lake Nicaragua Watershed (Cocibolca) : Addressing Key Environmental Challenges - World Bank (Washington, DC, 2014)
This study, policy and investment priorities to reduce environmental degradation of the Lake Nicaragua watershed, has assessed the sources and the magnitude of the pressures that threaten Lake Cocibolca. It was accomplished by applying a hydrological and land use model to the lake's watershed and by conducting additional estimates of nutrients generated from wastewater sources and tilapia farming. The study has confirmed that sediment loads are very high, and has estimated their magnitude in each sub-watershed. The key results of the study are the estimation of sedimentation levels in the watershed and the identification of erosion hotspots. The Lake Cocibolca watershed is a globally unique cradle of biodiversity with major importance not only to the global and local environment, but also to the 750,000 people living within its boundaries. Several fish species are endemic to the lake, and the watershed's location within the Mesoamerican Biological Corridor has made it a meeting ground for fish, bird and mammal species from North and South America. Apart from its importance for fishing and recreation industries, the lake is beginning to be used as a source of water supply for some coastal towns; its role as a source of drinking water may grow in the future. Lake Cocibolca and its watershed are under pressure from multiple sources but, in the absence of reliable monitoring information, the extent of the environmental degradation is unclear. Environmental deterioration in the watershed is high on the government's agenda.